Composition modification of electroplated nickel interlayer on tungsten carbide substrate by thermal carburizing - Wahab, H.; Noordin, M.; Izman, S.; Kamdi, Z.; Kurniawan, Denni (2014)
Nickel enables nucleation and growth of well oriented diamond crystals from the small lattice mismatch between nickel and diamond. However, its solubility for carbon causes carbon loss during diamond deposition and, consequently, results in poor nucleation density. In this study, carburizing of Ni/WC-Co specimens in high temperature furnace with inert gas atmosphere was adopted to provide nickel with sufficient carbon prior to diamond deposition. This process was carried out using charcoal powder as source of carbon at different treatment temperatures (750°C and 850°C) and durations (20min and 60min). Effect of the process in altering the nickel layer composition was characterized by microscopy, element analysis, and phase identification techniques. Results show that carburization leads to formation of metallic phases, such as nickel carbide and nickel cobalt, which are considered beneficial for diamond nucleation and growth. © (2014) Trans Tech Publications, Switzerland.